Information, Support, and Follow-up Offered to Women Who Experienced Severe Maternal Morbidity. Issue 1 (March 2019) - Furniss, M.; Conroy, M.; Filoche, S.; MacDonald, E.J.; Geller, S.E.; Lawton, B.
Abstract : ( Int J Gynaecol Obstet . 2018;141:384–388) Severe maternal morbidity (SMM) refers to a woman who nearly died but survived a complication that occurred during pregnancy, childbirth, or the postpartum period. It has been shown that women who experience an SMM event are at increased risk of postpartum morbidities, such as depression, and often need additional support on hospital discharge. In New Zealand, a recent review identified potential substandard care regarding certain components of care for women who experienced an SMM event. Therefore, the authors of the present study thus examined whether or not women who have experienced an SMM event were offered debriefing and a detailed discharge letter, a psychosocial report, and a follow-up opportunity with a clinical care specialist before discharge from hospitals in New Zealand.